JJCO Best Reviewer Award (Japanese Journal of Clinical Oncology, 2020)
Background The prognostic significance of the location of the primary tumor in upper tract urothelial carcinoma (UTUC) remains controversial. We evaluated the impact of ureteral urothelial carcinoma (UUC) versus renal pelvic urothelial carcinoma (RPUC) on oncological outcomes and recurrence patterns following radical nephroureterectomy (RNU). Methods We retrospectively analysed 779 patients with UTUC who underwent RNU between 2012 and 2021 within the JIKEI-YAYOI Collaborative Group. Propensity score matching (PSM) was performed to balance clinicopathological characteristics between UUC and RPUC. The primary endpoints were non-urothelial tract recurrence-free survival (NUTRFS) and overall survival (OS). Cancer-specific survival (CSS), intravesical recurrence-free survival (IVRFS), and recurrence patterns were also evaluated. Results After PSM, 309 matched pairs were analysed. Compared to RPUC, UUC was associated with significantly shorter NUTRFS (3-year rate: 68.9% vs. 77.6%, P = 0.048), OS (76.4% vs. 83.3%, P = 0.021), and CSS (80.0% vs. 88.1%, P = 0.009). No significant difference was observed in IVRFS (P = 0.90). Stage-specific analyses demonstrated that the adverse prognostic impact of UUC was primarily confined to patients with pT3/4 disease. Among node-negative pT3/4 patients, UUC was associated with significantly worse NUTRFS, OS, and CSS. Recurrence pattern analyses revealed higher rates of local recurrence and regional lymph node recurrence in pT3/4 UUC, whereas pulmonary metastasis was more frequent in RPUC. Conclusion Primary tumor location was significantly associated with oncological outcomes in UTUC. The prognostic disadvantage of UUC is mainly observed in locally advanced disease and appears to be driven by an increased risk of locoregional recurrence. Tumor location may provide additional prognostic information for postoperative risk stratification and surveillance planning.